Metastatic Intranasal Mastocytoma in a Dog - Schallenberger da Silva, Rúbia; Webber Klaser, Bruno; Fappi Scherer, Isadora; Davi dos Santos , Ezequiel; Garcia , Cinthia; Eduardo Bortolini, Carlos; Machado Costa , Márcio (Acta Scientiae Veterinariae, 2023)
Background: Mast cell tumors (MCTs) are neoplasms originating from mast cells, which can be well or poorly differentiated. They are considered the most commonly diagnosed malignant cutaneous neoplasm in dogs; however, intranasal forms are still little reported. Thus, this study seeks to report a case of unilateral intranasal MCT exhibiting submandibular lymph node metastasis. Case: A 11-year-old-and-4-month-old dog of undefined breed (UB), weighing 41 kg, was referred to the Veterinary Medical Teaching Hospital of the University of Passo Fundo (UPF), in the state of Rio Grande do Sul, Brazil. Presenting a clinical history of bilateral purulent nasal secretion, accompanied by sneezing in the two months prior to admission, in addition to vomiting and diarrhea. Auxiliary tests were requested, including skull X-ray, cytology of the nasal cavity with a swab, and collection of material from the submandibular lymph node directly through cytology with a needle. Cytological findings from the right nasal cavity were consistent with mast cell tumors (MCTs). Cytological analysis of the left nasal cavity was compatible with dysplasia/cellular reactivity. A heterogeneous population of cells was detected on cytology of the right submandibular lymph node. These findings were consistent with MCT lymph node metastasis. Skull radiography showed an increase in both opacity and soft tissue extension, surpassing the palate, from the canine tooth through the caudal region of the maxillary sinuses to the last molar, without bone destruction. The dog was then admitted for an abdominal ultrasound, which showed no changes in the spleen or liver. The leukocyte count showed mild lymphopenia and the presence of reactive lymphocytes. Through the buffy coat, the presence of rare round cells, compatible with circulating mast cells, was detected. Due to the biological behavior of the neoplasm and its anatomical location, the established therapy was based on the use of vinblastine and prednisolone. The patient did not show any clinical improvements. In a joint decision with the patient’s guardian, the dog was euthanized. Discussion: Intranasal MCTs commonly present progressive and intermittent unilateral epitaxis, mucopurulent nasal discharge, dyspnea, and ocular discharge. Several anatomical sites were associated with more aggressive neoplastic phenotypes; those with an unfavorable prognosis were mainly those present in the oral and intranasal mucosa. Cytopathological examination is considered a highly sensitive method for the diagnosis of MCTs. Metastases are present in more than 90% of mucosal MCTs, usually affecting regional lymph nodes and associated with a poor prognosis. Radiography is considered a useful test in determining the size and location of tumors in the nasal cavity. Chemotherapy plays an important role in the treatment, especially in cases like the one described in this report, in which surgical excision is not possible due to the anatomical location of the neoplasm. Intranasal MCTs are uncommon in dogs. In this case, he presented aggressive, metastatic behavior and a poor response to antineoplastic therapy. Furthermore, due to the location of these tumors, they may be clinically similar to a number of other upper respiratory tract diseases, posing a diagnostic challenge. Therefore, it is essential that the search for differential diagnoses be carried out through auxiliary tests, such as cytology and imaging. Keywords: neoplasm, cytology, diagnosis, chemotherapy.